Effects of restraint stress and high-fat diet on osseointegration of titanium implants: an experimental study - Dundar, Serkan; Bozoglan, Alihan; Bulmus, Ozgur; Tekin, Samet; Yildirim, Tuba Talo; Kirtay, Mustafa; Bozoglan, Merve Yilmaz (Sociedade Brasileira de Pesquisa Odontologica, 2020)
This study aimed to investigate the effects of chronic restraint stress (RS) and a high-fat diet (HFD) on the osseointegration of titanium implants in a rat model. After the surgical insertion of titanium implants into the metaphysis of the tibial bone, the rats were randomly divided into four equal groups (n = 8 each): control (CNT), restraint stress (RS), high-fat diet (HFD), and restraint stress plus high fat diet (RS-HFD). CNT: Rats received no further treatment during the 92-day experimental period. RS: Stress was applied to the rats beginning from two days after the implant surgery for one hour per day for the first 30 days, two hours per day for the next 30 days, and three hours per day for the last 30 days. HFD: Rats were fed a HFD for the following 90 days starting two days after surgery. RS-HFD: Rats were fed a HFD and RS was applied to rats for the following 90 days, starting two days after surgery. At the end of the experimental period, the rats were euthanized, and the implants and surrounding bone tissues were removed for histological analysis. Statistical analysis was performed by one way ANOVA and Bonferrroni tests. There were no significant differences in the bone-implant connection levels between the groups (p > 0.05), but in the HFD and RS-HFD groups, the bone filling ratios were found to be lower compared with the controls (p < 0.05) The data analyzed in this study suggest that an HFD with or without chronic RS adversely affected bone tissue in the rats during the 90-day osseointegration period.
Keywords: Hydrocortisone; Diet; High-Fat; Osseointegration; Bone-Implant Interface